Physico-chemical characterization of natural lake pigments obtained from Caesalpinia Sappan Linn. and their composite films for poly(lactic acid)-based packaging materials - Sutinee Girdthep (2018)
© 2018 Elsevier Ltd A newly colored biodegradable PLA-based film was fabricated from a compatibilized poly(lactic acid) poly(butylene adipate-co-terephthalate) blend (PLA/PBAT/TBT) using the natural lake pigment of Sappan. The natural lake pigment of Sappan was prepared as a Sappan colorant-adsorbed kaolinite (S-KT). S-KT composite in the form of an insoluble pigment and was prepared via co-precipitation and adsorption under basic conditions. It had a pinkish-red color and a maximum absorption of 516 nm. The stability of the natural lake pigment was improved and was confirmed by the improvement of the initial and maximum degradation temperatures from the TGA results, which could be attributed to the electrostatic attraction due to the process of chelation. The chelation that occurred between the Al(III) ion, the oxygen atoms of kaolinite surface and the brazilein molecules was proposed. The influence of S-KT content in the compatibilized blended films, known as S-KT composite films, was investigated by comparison with the KT composite film and the film without fillers. When the content of S-KT increased, the S-KT composite films exhibited a darker pinkish-red color. The mechanical properties in terms of strength increased due to KT acting as a nucleating agent with a 92% increase in the heat of crystallization in the S-KT7 film when compared with the film without fillers. The exfoliated-intercalated structure of S-KT resulted from the KT platelet disaggregation by brazilein adsorption and the intercalating of Al3+cations chelation as a hybrid interaction on the KT surface, which was indicated by the SEM. In addition, S-KT composite film could effectively resist heat at high temperatures with the maximum degradation temperature ranging from 337 to 393° C. This occurred as a result of KT clay acting as a superior insulator. Based on these results, the natural lake pigments presented the potential to be employed in the biodegradable polymer and could be used as a substitute for more toxic pigments. The biodegradable PLA-based colored films described here have a potential to be used in packaging applications. They offer the potential to increase the value-added appeal of products, with the benefit of being considered environmentally friendly by the consumer.